Meningkatkan keterampilan berbahasa Indonesia siswa melalui penerapan pembelajaran berbasis proyek - Saksi Tarigan (Indonesian Journal of Educational Development, 2021)
This study applies a project-based learning model as an effort to improve students' Indonesian language skills in the observation report material. This classroom action research took place in two cycles. The research was conducted at SMA Negeri 1 Kabanjahe from September 2019 to November 2019. The research subjects were all students of class X MIPA-2 SMA Negeri 1 Kabanjahe in the 2019/2020 academic year, totaling 32 students. The object of research is Indonesian language skills. The results showed: 1) the students' Indonesian language skills on the material of the observation report increased in the first cycle, showing an average of 69, with classical learning completeness of 46.88% and in the second cycle showed an average of 89 with classical completeness of 90.63 % or an increase of 44%; 2) student learning activities increased in the first cycle including reading and writing 37%, working on worksheets 32%, asking fellow friends 21%, asking questions to the teacher 5%, and 5% irrelevant to teaching and learning activities. Meanwhile, according to observations in Cycle II, among others, reading and writing 32%, doing worksheets 35%, asking fellow friends 21%, asking questions to the teacher 9%, and 3% irrelevant to teaching and learning activities. Thus the application of the project-based learning model can improve Indonesian language skills and student learning activities in two cycles. Penelitian ini menerapkan model pembelajaran berbasis proyek sebagai upaya untuk meningkatkan keterampilan berbahasa Indonesia siswa pada materi laporan hasil observasi. Penelitian tindakan kelas ini berlangsung dalam dua siklus. Penelitian dilaksanakan di SMA Negeri 1 Kabanjahe bulan September 2019 sampai dengan bulan November 2019. Subjek penelitian adalah seluruh siswa kelas X MIPA-2 SMA Negeri 1 Kabanjahe tahun pelajaran 2019/2020 yang berjumlah 32 siswa. Objek penelitian adalah keterampilan berbahasa Indonesia. Hasil penelitian menunjukkan: 1) keterampilan berbahasa Indonesia siswa pada materi laporan hasil observasi meningkat pada siklus I menunjukkan rata-rata 69, dengan ketuntasan belajar secara klasikal sebesar 46,88% dan pada siklus II menunjukkan rata-rata 89 dengan ketuntasan klasikal 90,63% atau terjadi peningkatan 44%; 2) aktivitas belajar siswa meningkat pada siklus I antara lain membaca dan menulis 37%, mengerjakan LKS 32%, bertanya sesama teman 21%, bertanya kepada guru 5%, dan yang tidak relevan dengan kegiatan belajar mengajar 5%. Sedangkan menurut pengamatan pada Siklus II antara lain membaca dan menulis 32%, mengerjakan LKS 35%, bertanya sesama teman 21%, bertanya kepada guru 9%, dan yang tidak relevan dengan kegiatan belajar mengajar 3%. Dengan demikian penerapan model pembelajaran berbasis proyek (project based learning) dapat meningkatkan keterampilan berbahasa Indonesia dan aktivitas belajar siswa dalam dua siklus.